Pengaruh Pola Pikir Kewirausahaan, Lingkungan Kerja, Efikasi Diri Terhadap Kinerja Karyawan - Baskoro Putra, Dimas; Tiarapuspa, Tiarapuspa (Rifa'Institute, 2023)
The purpose of this study is to analyze the effect of Entrepreneurial Mindset, Work Environment, Self Efficacy on Employees Performance at PT.HINO in Jakarta. Data were collected from one hundred and sixty HINO employees in Jakarta and the data collection technique used was purposive sampling. Hypothesis testing used in this study is using Multiple Regression analysis. The results of hypothesis testing in this study indicate that there is a positive effect of Entrepreneurial Mindset, Work Environment, Self Efficacy, on Employees Performance. The managerial implications in this study are how entrepreneurial thoughts, work environment and self-efficacy are very important in group and organizational life. Employees who apply an entrepreneurial mindset and self-efficacy to their work and duties and have good performance can affect the progress of a company or organization. Managers are expected to make employees think like entrepreneurs and be aware of their efficacy to create a good work environment and can improve employee performance at PT HINO in East Jakarta. This research is expected to make managers and further researchers think that the progress of employee performance is supported by many influences on the employees themselves and what makes employees enthusiastic in carrying out their duties or obligations